Study on the Dynamic Response Characteristics of Cylindrical Coal-Rock Samples under Dynamic Loads - Hongqing Zhu; Shuhao Fang; Yilong Zhang; Yan Wu (Shock and Vibration)
To research the dynamic response characteristics of cylindrical coal-rock samples under impact loads, the impact of rigid bars on cylindrical coal-rock samples is simulated under different speed conditions, based on LS-DYNA software, and the dynamic distribution characteristics of the stress, strain, and energy of cylindrical coal-rock samples are analyzed. The results demonstrated the following: (1) the cylindrical coal-rock sample failed at the center first, and the damage developed downward along the axial direction. (2) The critical effective stress and strain have an exponential function relationship with the velocity, and the critical time has a linear relationship with the velocity. (3) The energy change law of the cylindrical coal-rock sample is consistent with the destruction morphology. (4) The axial stress peaks in the severe damage part have a linear relationship with the speed, the axial stress attenuates rapidly after passing the stress yield point, and the axial strain does not increase continuously. (5) The peaks stress and strain on the central axis and the radial line obey the power function distribution, the axial stress produces tensile stress in the axial propagation direction, and the axial stress and strain peaks at the same position are larger than those of the radial stress and strain peaks. This research provides a reference for studying coal and rock dynamic disasters.